(untitled) (Innovation in Woodworking Industry and Engineering design, 2019)
The article deals with the issue of native sycamore maple wood and thermally modified sycamore maple wood milling on CNC machining centers. The milling of thermally modified wood is a very broad topic that deserves attention. The acquired knowledge concerning on the milling process may assist manufacturers improving the efficiency and quality of the process. Article based on experiments in which was at 5 axis CNC machining center milled 30 mm thick sycamore maple board. In the milling process they were used finishing cutters LEUCO VFW 178354. The mean arithmetic deviation of the roughness profile was investigated during cylindrical milling of the board edges. This article focuses on finding the differences in the roughness of wood surfaces after surface milling of native sycamore maple wood and thermally modified sycamore maple wood and differing feed speeds (1-10 m.min-1). In comparison with natural wood, thermal treatment had a negative effect on the quality of the wood surface after milling. The results also demonstrated an increased quality of surface finish with a decrease in feed speed.